Wind field retrieval over the ocean by HH polarization terraSAR-X data - Ren, Yongzheng; He, Mingxia; Lehner, Susanne (2010 International Conference on Multimedia Technology, ICMT 2010, 2010)
A new X-band wind field algorithm (XMOD) based on a linear approach is discussed in another paper to describe the relationship between normalized radar cross section (NRCS), wind speed, wind direction and incidence angle. But XMOD could only be applied with VV polarization SAR data. To be use the HH polarization SAR data, two C-band polarization ratio models were analysed and modified to X-band. To demonstrate the applicability of the two models, 10m height wind speeds were computed with XMOD from several VV/HH TerraSAR-X images and validated by QuikScat and DWD model results. In addition, the wind speeds were retrieved and compared to each other from the HH and VV polarization TerraSAR-X images of the same scene at the same time. ©2010 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: NRCS; Polarization ratio; TerraSAR-X; Wind field; XMOD